Review of ticks of the order Mesostigmata parasitic on reptiles - V. R. Saitov; A. H. Gubeidullina; A. I. Golubev; M. M. Salnikova; L. V. Malutina; N. V. Shakurova; I. R. Nigmetzyanov; A. S. Elovitskaya; G. S. Kashevarov; K. A. Yusupova; A. N. Siben; E. A. Efremova; et al. (Юг России: экология, развитие)
Aim. Analyse, summarise and characterise the current state of the world fauna of ticks of the order Mesostigmata parasitic on reptiles.Descriptive analysis based on data from Russian and foreign acarologists was used to study the current species diversity of ticks which are representatives of the families: Entonyssidae, Heterozerconidae, Ixodorhynchidae, Laelapidae, Macronyssidae, Paramegistidae, Omentolaelapidae from the order Mesostigmata, which parasitise reptiles.A chronological analysis was conducted and the results of acarological studies of the species of ticks parasitising reptiles were summarised. Supplementary information on new species of ticks and hosts-feeders was compileded. Various levels of host-parasite specificity, localisation of parasites, distribution width and endemicity are shown. The tick Ophionyssus natricis was found to be the most representative species: a parasite of snakes and lizards, widely distributed throughout the world, both on domestic (zoo) and wild reptiles and are capable of attacking other vertebrates, including humansAwareness of the current state of knowledge of the tick parasitic fauna on reptiles will contribute to updating of the scientific database, expansion of research horizons, increase in the level of research and teaching activities and the dissemination of knowledge on the wide species diversity and distribution of various groups of ticks.